Os resultados do incentivo ao empreendedorismo como estratégia de desenvolvimento socioeconômico no Brasil - Otto, Igor Montenegro Celestino (2021)
Entrepreneurship has been pointed out as a strategy for socio-economic development, both in theoretical thought and in the political-institutional field. Guided by this ideal, several countries worldwide have adopted public policies in the last decades as instruments to boost entrepreneurship, aiming to promote development in their countries. In this context, this study aims to demonstrate the profile of small businesses in Brazil between the years 2015 and 2019, considering the results achieved by entrepreneurship incentive public policies focused on development, in particular, the General Law of Micro and Small Businesses. For this purpose, an exploratory, documentary research was conducted using data obtained from the statistics of the Ministry of Economy, the Brazilian Institute of Geography and Statistics (IBGE), and the Brazilian Micro and Small Business Support Service (Sebrae). The data was organized into categories to improve understanding of the policy outcomes. The current model of public policies to encourage entrepreneurship seems to have been exhausted, as there is a clear stagnation of the participation of small businesses in the Value Added to the Gross Domestic Product. Furthermore, it was not possible to demonstrate that entrepreneurship promotes the country's socioeconomic development because the data showed that small Brazilian businesses remain mostly informal, with low productivity, and generating little income for entrepreneurs